Quantitative measure of asymptomatic cardiovascular disease risk in Type 2 diabetes: Evidence from Indian outpatient setting - Ghosal, Samit (Indian Heart J, 2020)
BACKGROUND: The cardiovascular (CV) risk of patients with Type 2 diabetes (T2D) of Indo-Asian descent has never been objectively assessed, although it is documented that they have a higher prevalence of CV disease (CVD). AIMS: To identify groups of Indian patients with asymptomatic T2D who are at high risk of CVD as per the QRISK calculator. METHOD: After an adequate power calculation, a nation-wide study of patients with asymptomatic T2D was conducted. The QRISK3 scores of these patients were used to derive a 10-year risk of CV events. High CVD risk was defined as ≥20% risk of CV event in 10 years. RESULTS: For a total of 1538 patients across 154 outpatient departments, the QRISK3 scores were collated. Median 10-year CVD risk was 22.2%. Mean 10-year CVD risk was 28.4% (standard deviation 22.1%), representing a 5.7-fold increase vs. controls (i.e., matched healthy adults). Absolute CVD risk increased linearly with age. Over 50% of T2D males aged above 45 years had a high (>20%) CVD risk. Women aged more than 55 years had a high risk of CVD. More than 50% of patients with a T2D duration of more than 5 years had a high risk of CVD as per the QRISK3 calculator.